2018
DOI: 10.1002/brb3.921
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin protects neural cells against ischemic injury in N2a cells and mouse brain with ischemic stroke

Abstract: Background and PurposeCurcumin, a natural antioxidant isolated from Curcuma longa, has been reported to exert neuroprotective effect in animal models of ischemic stroke. However, the underlying mechanism is still not fully understood. The purpose of this study was to investigate the effect of curcumin treatment on neuronal apoptosis in the periinfarct cortex after cerebral ischemia/reperfusion (I/R) injury and in mouse N2a cells after oxygen‐glucose deprivation/reoxygenation (OGD/R) injury and its underlying m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 47 publications
(80 reference statements)
5
35
0
Order By: Relevance
“…In the same model, curcumin administration reduced neuroinflammation by lowering the IL6, TNFα [117,121], and iNOS levels, and mediating autophagy activity via PI3K/Akt/mTOR [117,119]. Results similar to those described for rats were also obtained in a mouse model of local cerebral ischemia, in which administration of curcumin reduced cerebral infarction and neuronal apoptosis most likely by limitation of mitochondrial dysfunction [127]. In addition, curcumin has been found to improve neurological function score, maintain the integrity of the blood-brain barrier, and reduce the infarct volume of the cerebral cortex, and decrease mortality, as well as apoptosis of neurons in animal brain ischemia models [128][129][130].…”
Section: Neuroprotection and Neurogenesissupporting
confidence: 60%
“…In the same model, curcumin administration reduced neuroinflammation by lowering the IL6, TNFα [117,121], and iNOS levels, and mediating autophagy activity via PI3K/Akt/mTOR [117,119]. Results similar to those described for rats were also obtained in a mouse model of local cerebral ischemia, in which administration of curcumin reduced cerebral infarction and neuronal apoptosis most likely by limitation of mitochondrial dysfunction [127]. In addition, curcumin has been found to improve neurological function score, maintain the integrity of the blood-brain barrier, and reduce the infarct volume of the cerebral cortex, and decrease mortality, as well as apoptosis of neurons in animal brain ischemia models [128][129][130].…”
Section: Neuroprotection and Neurogenesissupporting
confidence: 60%
“…These data were confirmed in a HUVECs cellular model, where curcumin treatment attenuated H 2 O 2 -induced oxidative stress [81]. Similar results were obtained from other animal and cellular models: curcumin treatment reduced cerebral infarction and neuronal apoptosis in a mouse model of middle cerebral artery occlusion (MCAO), and in N2a cells, it reduced mitochondrial dysfunction [86]. Moreover, using the MCAO rat model, it was observed that curcumin reduced infarct volume [87] and brain oedema at 24 h [88], prevented the development of post-ischemic neurodegeneration [89], and treated rats achieved better neurological scores compared to untreated rats [90,91].…”
Section: Strokesupporting
confidence: 79%
“…The anti-inflammatory and anti-apoptotic effects of curcumin were reported previously [22,23]. Curcumin's neuro-protective effects were also found in many neuro-pathological models, including cerebral I/R in vivo and in vitro models [24,25]. Many mechanisms underlying curcumin's neuro-protective effects have been proposed.…”
Section: Discussionmentioning
confidence: 76%